The first finding of Ostrea cf. puelchana (Bivalvia) living as epibiont on Callinectes exasperates (Decapoda) - Silvio Felipe Barbosa Lima; Rudá Amorim Lucena; Vinicius Queiroz; Carmen Regina Parisotto Guimarães; André Breves (Acta Scientiarum. Biological Sciences, 2017)
This paper describes the epibiosis of Ostrea cf. puelchana on Callinectes exasperatus (Gerstaecker, 1856), both collected from the estuary of the Paraíba River, in the state of Paraíba, northeastern Brazil. The basibiont crab was captured using a trap installed in mangrove area at a depth of about 2 meters. The oyster was closely attached to the left side of dorsal carapace covering most of the epibranchial, mesobranchial and metabranchial regions. Possible advantages and disadvantages for both the epibiont and the basibiont are discussed. We believe that young O. cf. puelchana may avoid a variety of potential predators due to the considerable movement capacity of C. exasperatus and may also serve as a small protective shield for the basibiont. However, the oyster, which is a bivalve with an epifaunal lifestyle, is likely to be negatively affected, mainly due to burrowing activity of the crab. This is the first record of epibiosis between bivalves of the genus Ostrea Linnaeus, 1758 and crabs of the genus Callinectes Stimpson, 1860.